Analysis of cohesion calls in "Orcinus orca" (Linnaeus, 1758) - Lalueza Broto, Estela (2016)
The killer whales emit emit vocal signals to maintain group cohesion. It is assumed discrete calls are used as cohesion calls, nevertheless has not been tested if any of them could be used for other reason. Combining different stereotyped discretes calls into specific sequences increases the probability to happen a call with response. The acoustic activity of five orcas (Orcinus orca) was monitored during five different nights and distributed in three pools, leaving one orca in pool A and the rest of the group between pools B and C. Out of 4311 classified vocalizations were obtained 632 call-response sequences between different pools.